Sejarah Pemikiran Ekonomi Islam pada Masa Rasulullah SAW dan pada Masa Khulafaur Rasyidin Beserta Perbedaannya - Perwira Hasibuan; Mhd. Rifq Alfahrezi; Ahmad Wahyudi Zein; Ilhamuddin Sianifar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Islamic economic thought has strong roots since the time of the Prophet PBUH and developed further during the time of Khulafaur Rashidin. This journal aims to analyze the differences in economic thinking and policies in the two periods. During the time of the Prophet, the main focus was to build an economic system based on sharia values such as justice, the prohibition of usury, and the implementation of zakat to create social solidarity. On the other hand, the Khulafaur Rasyidin period presented more complex challenges, such as the management of large areas, the distribution of wealth, and political stability. In this article, we discuss the economic policies of the caliphs in detail, including the formation of diwans, land management, and supervision of state financial administration. The study shows that the core values of Islamic economics remain consistent, but their implementation adapts to social, political, and economic dynamics. This research is expected to provide new insights into re...